2014
DOI: 10.3109/09546634.2013.869302
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind, randomized, placebo-controlled trial of oral isotretinoin in the treatment of recalcitrant facial flat warts

Abstract: Isotretinoin is an effective treatment for recalcitrant flat facial warts with a well-known, manageable safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
38
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 17 publications
7
38
1
Order By: Relevance
“…Vitamin A treatment may also increase or prolong expression of HPV T or B cell antigens, allowing clearance of warts by immune mechanisms . Our results support the previous findings that oral retinoids including acitretin and isotretinoin have been used with marked improvement in the management of extensive and recalcitrant warts . Additionally, retinol possesses antioxidant activities .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Vitamin A treatment may also increase or prolong expression of HPV T or B cell antigens, allowing clearance of warts by immune mechanisms . Our results support the previous findings that oral retinoids including acitretin and isotretinoin have been used with marked improvement in the management of extensive and recalcitrant warts . Additionally, retinol possesses antioxidant activities .…”
Section: Discussionsupporting
confidence: 89%
“…5 Our results support the previous findings that oral retinoids including acitretin and isotretinoin have been used with marked improvement in the management of extensive and recalcitrant warts. [18][19][20][21][22] Additionally, retinol possesses antioxidant activities. 23 Micronutrient deficiencies, especially zinc deficiency that is commonly reported in recalcitrant warts patients, 24 reduces circulating retinol, causing a functional vitamin A deficiency even with sufficient liver stores.…”
Section: Discussionmentioning
confidence: 99%
“…studied the effect of oral isotretinoin in facial flat warts and concluded that all patients in the oral isotretinoin group showed complete clearance, whereas none in the placebo group showed any improvement. The most frequent side effect was cheilitis …”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that the topical proprietary formulation consisting of 1% cantharidin, 5% podophyllotoxin, and 30% salicylic acid (CPS) has achieved complete clearance of RPW in 100% of patients . This is a high cure rate compared to other treatments but it's a preliminary study. Despite its regular clinical use and reported safety , inadequate data currently exist to modify the FDA status of cantharidin or reassure institutions of its safety .…”
Section: Introductionmentioning
confidence: 94%